Analisis Kebutuhan Pengembangan Media Komik Digital untuk Memahami Kausalitas Peristiwa bagi Siswa SMA - Septiani, Fadilla; Aisiah, Aisiah (Jurnal Kronologi, 2025)
History learning needs to be supported by media that can visualize historical events. However, the visual media used in history learning are still lacking in variety. The purpose of this study is to analyze the need for developing history learning media in the form of digital comics to train students in understanding the causality of historical events. This study employed a mixed methods approach. The data were obtained from 36 tenth-grade students of MAN 1 Kota Bukittinggi and one history teacher. Data collection was carried out through three test items, classroom observations, and interviews. Quantitative data were analyzed using percentage formulas, while qualitative data were analyzed descriptively. The findings of the study show that: first, students’ ability to analyze the causality (cause-and-effect) of historical events in the topic of Hindu-Buddhist kingdoms is low, as seen from the test results. A total of 69% of students answered the first question correctly, 52% the second, and 41% the third. Second, interview results indicate that technology-based visual media are still rarely used by history teachers. Third, history teachers face technical challenges in creating varied learning media, especially digital-based visual media in the form of digital comics. These findings highlight the need to develop digital comic media that can help students understand the cause-and-effect (causality) relationships of historical events related to the Hindu-Buddhist kingdoms in Indonesia.